Longitudinal physiological and fitness evaluations in elite ice hockey: a systematic review - Chiarlitti, N. A.; Crozier, M.; Insogna, J. A.; Reid, R. E.; Delisle-Houde, P. (The Journal of Strength and Conditioning Research, 2021)
Ice hockey has greatly evolved since the last review article was published more than 25 years ago. Although players still combine anaerobic and aerobic conditioning, the pace of the game has greatly increased. Players are faster, stronger, and more agile than their predecessors; however, an important emphasis is now placed on maximizing player performance for the play-offs. For the coaching staff, strength and conditioning coaches, and players, an emphasis on mitigating fitness and physiologic losses throughout the season would be beneficial, given the intimate relationship they share with on-ice performance. This systematic review of the literature outlines the current knowledge concerning longitudinal changes in relation to fitness, body composition, and physiologic parameters across an elite hockey season. The search of 4 large scientific databases (i.e., Embase, PubMed, SPORTDiscus, and Web of Science) yielded 4,049 items, which, after removing duplicates and applying inclusion and exclusion criteria, resulted in 23 published scientific articles to be included in this review. The wide span of literature (1956-2020) made inferences difficult giving the degree to which the game of ice hockey has changed; however, more recent research points to an aerobic deconditioning pattern and increased fatigue throughout the season in a specific group of elite hockey players (i.e., university athletes) while showing that ice hockey can lead to many possible histological adaptations. Ultimately, tracking, identifying, and developing methods to mitigate potential negative longitudinal changes will be imperative to influencing individual and team performance in the later parts of the season.